A CIDR-based AI protocol establishes pregnancy in repeat-breeder dairy cattle - HONPARKHE, M; GHUMAN, S P S; SINGH, JAGIR; DHALIWAL, G S (The Indian Journal of Animal Sciences, 2011)
The objectives of this study were to document ovarian and endocrine responses as well as pregnancy establishment following the treatment of repeat-breeder crossbred dairy cattle with a progesterone-releasing controlled internal drug release (CIDR) -based artificial insemination (AI) protocol. Cattle (25) received prostaglandin F2a (PGF2a , 500μg) on day 0, concurrent with the intravaginal placement of CIDR (1.38 g progesterone) for 15 days, followed by gonadotropin releasing hormone (GnRH) analogue (20μg) administration at the spontaneous onset of estrus (day 17, 18 or 19). About 10 h after GnRH, AI was carried out in all the cattle. On day 0, a corpus luteum (CL, 13.7±1.4 mm) and a large follicle (11.1±0.6 mm) were detectable in all the cattle. On day 15, the former was regressed (P<0.05), whereas the latter disappeared completely in all the animals. Estrus detection was carried out daily subsequent to CIDR removal. All the cattle exhibited onset of estrus between 48–96 h after CIDR removal. The preovulatory follicle observed at the time of AI (15.0±0.5 mm) ovulated in all the cattle (P<0.05) between 72–120 h after CIDR removal (or 24–48 h after GnRH). First service conception rate was appreciably greater (52%, P<0.05) in comparison to 0% conception rate of all the cattle during their previous AIs (4.2±0.2). Retrospective analysis suggested that cattle failing to conceive had persistently higher (P<0.05) luteal activity on the day of AI compared to their conceiving counterparts. In conclusion, a CIDR-based (PGF2a +CIDR-GnRH) based AI protocol is highly successful for inducing ovulation in the repeat-breeder (due to endocrine dysfunctions) cattle, and resulted in an acceptable conception rate.